2014
DOI: 10.3747/co.21.1769
|View full text |Cite
|
Sign up to set email alerts
|

Use of Dexamethasone in Patients with High-Grade Glioma: A Clinical Practice Guideline

Abstract: phd, || and the Alberta Provincial CNS Tumour Team• Patients who have high-grade tumours, are symptomatic, or have poor life expectancy, can be maintained on a 0.5-1.0 mg dose of dexamethasone daily.• Side effects with dexamethasone are common, and they increase in frequency and severity with increased dose and duration of therapy. Patients should be carefully monitored for endocrine, muscular, skeletal, gastrointestinal, psychiatric, and hematologic complications, and for infections and other general side eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
112
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(119 citation statements)
references
References 32 publications
2
112
1
4
Order By: Relevance
“…It has been reported that GC may affect growth and chemosensitivity of carcinoma cells via diverse mechanisms. Dexamethasone (Dex) is a synthetic GC, which is often used in clinic to treat all kinds of diseases (Kostaras et al, 2014;Sau et al, 2014), such as breast cancers. For example, Nakayama et al found that combination of palonosetron and Dex was an antiemetic treatment of choice for patients with breast cancer treated with anthracycline (Nakayama et al, 2013).…”
Section: Dexamethasone Disrupts Cytoskeleton Organization and Migratimentioning
confidence: 99%
“…It has been reported that GC may affect growth and chemosensitivity of carcinoma cells via diverse mechanisms. Dexamethasone (Dex) is a synthetic GC, which is often used in clinic to treat all kinds of diseases (Kostaras et al, 2014;Sau et al, 2014), such as breast cancers. For example, Nakayama et al found that combination of palonosetron and Dex was an antiemetic treatment of choice for patients with breast cancer treated with anthracycline (Nakayama et al, 2013).…”
Section: Dexamethasone Disrupts Cytoskeleton Organization and Migratimentioning
confidence: 99%
“…Corticosteroids such as dexamethasone have been routinely used in the management of cerebral oedema in patients with brain tumours, meningitis, haemorrhagic stroke and cerebral ischemia [11][12][13][14][15][16][17][18] due to due to their long half-lives and their relatively low mineralocorticoid effects, thereby minimizing sodium and water retention [19,20]. Dexamethasone acts on the glucocorticoid receptor and is highly effective in reducing blood-brain barrier (BBB) permeability [21][22][23][24], inflammatory cascades [25][26][27] and oxidative stress [28][29][30][31] and in modulating Na + ,K + -ATPase activity [32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18] Dexamethasone, 4 mg to 24 mg per day, is commonly used for patients with diseaserelated cerebral edema. [19][20][21] While these doses may also provide antiemetic benefit, additional dexamethasone is likely unnecessary.…”
Section: Supportive Carementioning
confidence: 99%